Penyiapan Pengelolaan Pasca Rawat pada Pasien Stroke Hemoragik dengan Riwayat Peb: Case Report - Mutiarasani, Anjani; Kurniawan, Titis; Pratiwi, Sri Hartati (Universitas Malahayati, 2024)
ABSTRACT Post-hospitalization stroke patients include assessing and preparing patients and families to meet post-treatment needs is important. Aims to explain the needs of post-stroke patients with a history of preeclampsia along with efforts to prepare patients and their families to meet these needs. Case report used Morse fall scale, Braden scale, Readiness for hospital discharge scale (RHDS) and Barthel indeks instruments to identify the post- treatment needs od stroke patients with a history of preeclampsia who were undergoing treatment in the inpantient room of a Regional Hospital in West Java. Educational topics include: ROM (range of motion), personal hygiene, pressure ulcer prevention, and fall risk prevention and danger signs. One month after being discharged from the hospital, the patient has implemented ROM (range of motion), personal hygiene is fulfilled, there is no risk of pressure sores/falls. The Barthel index score one month after discharge from the hospital improved to 6 (severe dependence). Preparations for the postpartum period with a history of PEB are fulfilled by taking regular medication and caring for the baby. Post-treatment education and follow-up are activities that have the potential to be effective in improving the patient's ability to meet post-treatment needs. It is important for hospitals to maintain continuity of care through regular follow-up and coordination with families to ensure that post-treatment needs are met and anticipate complications due to stroke. Keywords: Case Report, Continue of Care, Post Treatment, , Preeclampsia, Stroke Hemoragic ABSTRAK Pasca rawat pada pasien stroke meliputi pengkajian dan penyiapan pasien dan keluarga untuk memenuhi kebutuhan pasca rawat merupakan hal yang penting. Bertujuan untuk memaparkan kebutuhan pasien pasca stroke dengan riwayat preeklampsia beserta upaya penyiapan pasien beserta keluarganya untuk memenuhi kebutuhan tersebut. Case study ini dengan instrument Morse fall scale, Braden scale, Readiness for hospital discharge scale (RHDS) dan Barthel indeks digunakan untuk mengidentifikasi kebutuhan pasca rawat pasien stroke dengan riwayat preeklampsia yang menjalani perawatan di Ruang Rawat Inap salah satu RS Daerah di Jawa Barat. Topik edukasi mencakup : ROM (range of motion), personal hygiene, pencegahan dekubitus, dan pencegahan risiko jatuh serta tanda bahaya. Satu bulan setelah keluar dari rumah sakit, pasien telah menerapkan ROM (range of motion), personal hygiene terpenuhi, tidak terdapat risiko dekubitus/jatuh. Skor Barthel indeks satu bulan setelah keluar dari rumah sakit membaik menjadi 6 (ketergantungan berat). Penyiapan pada postpartum dengan Riwayat PEB terpenuhi dengan minum obat rutin dan perawatan bayi. Edukasi dan follow up pasca rawat merupakan kegiatan yang berpotensi efektif memperbaiki kemampuan pasien memenuhi kebutuhan pasca rawat. Menjadi penting bagi rumah sakit untuk menjaga continue of care melalui follow up secara reguler serta koordinasi dengan keluarga untuk menjamin keterpenuhan kebutuhan pasca rawat dan antisipasi komplikasi akibat stroke. Kata Kunci: Case Report, Continue Of Care, Pasca Rawat, Preeklampsia, Stroke Hemoragik